The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/hon.2005
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib plasma trough levels in chronic myeloid leukaemia: results of a multicentre study CSTI571AIL11TGLIVEC

Abstract: Imatinib has been accepted as frontline treatment for patients with chronic myeloid leukaemia (CML), and patients generally receive doses ranging from 400 to 800 mg/day. Previous studies have demonstrated that maintaining imatinib plasma levels (IMPLs) >1000 ng/mL leads to improved responses and long-term outcomes. However, IMPLs vary among patients because of factors such as drug-drug interactions, adherence, toxicity and differential levels of expression of cellular efflux/influx proteins. In this study, IMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 22 publications
1
24
0
2
Order By: Relevance
“…[47][48][49] More recently, studies have indicated that higher imatinib plasma levels correlate with clinical responses and compliance, and also suggest that plasma levels are a means to assess drug toxicity and management of imatinib therapy in patients with CML. 61,62 Of interest, recently a self-assessment questionnaire received preliminary validation in patients with CML receiving imatinib treatment, allowing health care professionals to assess patient adherence during their routine clinical practice. 63 A study using MEMS ® over a 1-year period reported that adherence correlates to drug concentrations in plasma, thus indicating the successful use of electronically monitored dosing histories for modeling pharmacokinetic data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[47][48][49] More recently, studies have indicated that higher imatinib plasma levels correlate with clinical responses and compliance, and also suggest that plasma levels are a means to assess drug toxicity and management of imatinib therapy in patients with CML. 61,62 Of interest, recently a self-assessment questionnaire received preliminary validation in patients with CML receiving imatinib treatment, allowing health care professionals to assess patient adherence during their routine clinical practice. 63 A study using MEMS ® over a 1-year period reported that adherence correlates to drug concentrations in plasma, thus indicating the successful use of electronically monitored dosing histories for modeling pharmacokinetic data.…”
Section: Discussionmentioning
confidence: 99%
“…In support of the use of such markers, imatinib plasma levels may predict adherence and clinical response, and hence serve as a guide to optimizing therapy in CML patients. [47][48][49] More recently, studies have indicated that higher imatinib plasma levels correlate with clinical responses and compliance, and also suggest that plasma levels are a means to assess drug toxicity and management of imatinib therapy in patients with CML. 61,62 Of interest, recently a self-assessment questionnaire received preliminary validation in patients with CML receiving imatinib treatment, allowing health care professionals to assess patient adherence during their routine clinical practice.…”
mentioning
confidence: 99%
“…[21][22][23][24][25] Several studies have investigated whether the imatinib C 0 reflects the clinical response of patients taking imatinib, namely exposure-response relationships. 11,12,[20][21][22][25][26][27][28][29][30] In Japanese CML patients, we have reported that the imatinib C 0 was significantly higher in patients with a MMR than in those without a MMR; the mean values were 1107±594 ng/ mL and 873±529 ng/mL, respectively (p=0.002). 21) Picard et al first reported that a steady-state imatinib C 0 measured after at least 12 months of treatment with a standard imatinib dose correlated with the MMR, and the threshold for the imae-mail: m-miura@hos.akita-u.ac.jp tinib C 0 should be set above 1002 ng/mL.…”
Section: Imatinib Tdmmentioning
confidence: 90%
“…36) Furthermore, it has also been reported that there was no significant difference in the imatinib C 0 between patients who achieved a MMR (976±385 ng/mL) and a CMR (1138±809 ng/mL). 30) For CMR achievement, a higher imatinib C 0 was not necessary; however, the target imatinib C 0 should still be set above 1000 ng/mL. BCRP, encoded by the ABCG2 gene, is a membrane efflux transporter normally expressed in the small intestine and biliary canalicular front of hepatocytes, 37,38) which is involved in the absorption, distribution, and excretion of a wide variety of clinically relevant drugs.…”
Section: Imatinib Tdmmentioning
confidence: 99%
“…Many studies have been conducted to understand the relation of imatinib plasma concentrations with clinical response. [1][2][3] Imatinib is a targeted, potent and competitive TKI; it is designed to selectively interfere with key signal transduction pathways. [4][5][6] It performs its therapeutic activity on CML by competitive inhibition at the ATP-binding site.…”
Section: Imatinib and Norimatinib Plasma Levels Analyses Of Chronic Mmentioning
confidence: 99%